Periostin and mesothelin: Potential predictors of malignant progression in intrahepatic cholangiocarcinoma. Issue 5 (25th April 2018) - Mandrekar, Pranoti; Cardinale, Vincenzo
Abstract : This is an Editorial on 2 manuscripts Manzanares et. al. entitled "Overexpression of Periostin and Distinct Mesothelin Forms Predict Malignant Progression in a Rat Cholangiocarcinoma Model" and Mino et. al. entitled "Overexpression of Periostin and Distinct Mesothelin Forms Predict Malignant Progression in a Rat Cholangiocarcinoma Model" which summarizes the findings and highlights the potential of periostin and mesothelin as important mediators of malignancy in iCCA and their possible benefits as prognostic indicators.